P519 Post-surgical recurrence predictors in the years 2000. Results of a retrospective single-centre long-term follow-up series and impact of imaging findings on outcomes. (25th January 2019) - Mendolaro, M; Daperno, M; Randazzo, C; Lavagna, A; Mineccia, M; Cosimato, M; Bertolino, F; Rigazio, C; Ercole, E; Ferrero, A; Rocca, R
Abstract: Background: Post-operative recurrence of Crohn's disease (CD) after so-called curative ileocolonic resection is common. Early identification of features associated with recurrence and risk stratification could be essential for the postoperative management of these patients. The aim of the current study was to evaluate the impact of clinical variables and instrumental recurrence on long-term clinical and surgical recurrence. Methods: We report data of 125 consecutive patients with CD, undergone ileocolonic resection between July 2000 and January 2010 (median follow-up after surgery 9.4 ± 4.4 years) Clinical-demographic characteristics, post-surgical therapy, endoscopy recurrence (Rutgeerts' Score ≥ 2) and ultrasound features (bowel wall thickness ≥ 4 mm, loss of wall stratification, mesenteric hypertrophy) were recorded. Kaplan–Meier survival analysis was conducted to identify variables associated with recurrence-free survival (clinical and surgical), both in all patients and in those who performed endoscopy or ultrasound within 18 months after surgery. Time-dependent Cox regression analysis was carried out for multi-variate analysis. Results: Clinical recurrence occurred in 99 patients (80%); in 34/41 patients (83%) within 12 months and in 52/63 (83%) within 18 months. In 25 patients (31%) surgical recurrence was observed, in 3 (4%) cases within 12 months and 4 (5%) within 18 months. The only clinical variables significantly associated with outcomes were stricturing pattern for clinical recurrence and surgical indication for refractory disease for surgical recurrence. Endoscopic recurrence and selected US features were associated to clinical recurrence only. No clinical or imaging predictors were associated to clinical or surgical recurrence in multi-variate analysis. Conclusions: Early evaluation of US and endoscopic features predicts clinical outcomes, apparently not long-term surgical outcomes, in these retrospective series. Prospective long-term follow-up studies with uniform short-term evaluation and therapeutic management are advisable to explore the yields of prognostic prediction through endoscopy or ultrasound, especially in the biologic treatments era.